A flexible topo-optical sensing technology with ultra-high contrast - Cong Wang (Nature Portfolio, 2020)
Flexible materials with mechano-responsive luminescence has gained interest for their potential in sensing devices. Here, the authors demonstrate targeted folding under high compressive strains, which, together with the oxygen quenching of fluorophores, forms the basis for topo-optical sensing.